Unique Practice Technique: Introducing the Tarsal Twist Manipulation (International Journal of Physiotherapy, 2021)
Background: High-velocity low-amplitude thrust joint manipulations are interventions with a growing body of evidence supporting their use to manage spine pain; however, evidence is lacking to support joint manipulation to treat lower extremity pain. Cuboid manipulations, the most researched foot manipulation, have been included in the successful management of cuboid syndrome, posterior tibial tendinopathy, and iliotibial band pain. Yet, there are no clear reasons for how or why patients improve after a cuboid manipulation. The proposed mechanisms include biomechanical, neurophysiological, and/or placebo.Technique Summary: This Unique Practice Technique presents a novel tarsal manipulation, the Tarsal Twist, that can improve outcomes through a combination of mechanisms and be provided to patients in the acute, subacute, or chronic phases of healing. The Tarsal Twist is performed with the patient supine. The clinician performs a high-velocity, low amplitude thrust through the calcaneus and first metatarsal in the direction of forefoot inversion, calcaneal eversion, and forefoot abduction.Outcome Measures: While anecdotal evidence from the authors suggests this tarsal manipulation is effective, additional research needs to be performed to identify the true efficacy; therefore, this novel tarsal manipulation should be used in conjunction with the standard of practice.Conclusion: The Tarsal Twist provides clinicians with an additional option for treating patients with foot and ankle dysfunction and challenges the traditional cuboid manipulation technique.